(3OjhGf GdoeKbH GdYHOjs - (3GdoenKpqbH GdnYrHOj, GdYGFP Hf eMUf Hf KYdHg ef Hfj YHO GdbjS , fMh (B35 (3b g` s
(3ChdgG (B:s
(3gd YfO ZGmf daDGO nUpO ef fgdI aj Gdjhe Chai ZO s
(3BNQgG (B:s
(3hbGe HUdM Hf Yha hYGeQ hNWI aUd eG jYGH RYjegG s
(3fSNI cJH GdTYQ ajgG Hbde GdKdK hGdTQM Hbde GdfSNs
(3hYdjgG hba QFjS GdcJGH SfI (B1154(3g``s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B4s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B197 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs